Black holes, qubits and octonions - Borsten,L; Dahanayake,D; Duff,MJ; Ebrahim,H; Rubens,W (Physics Reports, 2009)
We review the recently established relationships between black hole entropy in string theory and the quantum entanglement of qubits and qutrits in quantum information theory. The first example is provided by the measure of the tripartite entanglement of three qubits (Alice, Bob and Charlie), known as the 3-tangle, and the entropy of the 8-charge black hole of supergravity, both of which are given by the invariant hyperdeterminant, a quantity first introduced by Cayley in 1845. Moreover the classification of three-qubit entanglements is related to the classification of supersymmetric black holes. There are further relationships between the attractor mechanism and local distillation protocols and between supersymmetry and the suppression of bit flip errors. At the microscopic level, the black holes are described by intersecting -branes whose wrapping around the six compact dimensions provides the string-theoretic interpretation of the charges and we associate the three-qubit basis vectors, , with the corresponding 8 wrapping cycles. The black hole/qubit correspondence extends to the 56 charge black holes and the tripartite entanglement of seven qubits where the measure is provided by Cartan’s invariant. The qubits are naturally described by the seven vertices of the Fano plane, which provides the multiplication table of the seven imaginary octonions, reflecting the fact that has a natural structure of an -graded algebra. This in turn provides a novel imaginary octonionic interpretation of the charges of : the NS–NS charges correspond to the three imaginary quaternions and the R–R to the four complementary imaginary octonions. We contrast this approach with that based on Jordan algebras and the Freudenthal triple system. black holes (or black strings) in five dimensions are also related to the bipartite entanglement of three qutrits (3-state systems), where the analogous measure is Cartan’s invariant. Similar analogies exist for magic supergravi